Factors affecting Accidental Toxic Ingestion Among Children Younger Than 5 Years - Ambreen Raza, Mahnaz Hakeem, Hafsa Zaheer, Sana Samreen, Falak Naz, Bushra Afroze (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction:One million children die each year from injuries around the world, with poisoning being the fourth most common cause.Children below five years are at an increased risk because of their exploratory nature and hand to mouth activity, accounting for 15% of accidental poisoning related deaths in this age group.A community oriented study that studiedthe national health survey of Pakistan reported that the incidence of accidental poisoning was 4.3% among children below five years. Objectives: To determine the socio-demographic factors affecting accidental toxic ingestion in children younger than five years at Aga Khan University Hospital, Karachi. Materials & Methods:A descriptive cross-sectional study was carried out at the emergency Deptof the Aga Khan University Hospital in Karachi, Pakistanbetween August 2016 to July 2017. Children with a history of accidental ingestion were included in the study. Descriptive statistics and Chi-square association was used employed using SPSS version 23. Results: A total of 97 children between the age group of 6 months – 5 years were enrolled, amongst 61 (62.88%) male. 74 (76.29%) children had unsafe storage of hazardous chemicals, 34 (35.05%) had large family size, 5 (5.15%), 3 (3.09%), and 3 (3.09%) of participants had lower socioeconomic status, uneducated, and rural residents respectively. Practical implication Conclusion: Awareness to parents regarding child protective strategies and usage of safe packaging in medicines may avoid accidental toxic ingestion. Keywords: Accidental poisoning, Socioeconomic Status, Education.